Association of Body Mass Index and Anemia with Dietary Diversity of Nursing Students in Chitwan, Nepal - Parajuli, Sumitra; Sharma , Sudha; Regmi, Kamala; Chaudhary, Tulasi; Aryal, Neelu; Poudyal, Jiwan Kumar (Journal of Bharatpur Hospital, 2025)
Background Adequate dietary diversity and nutritional status among nursing students are essential for a healthy lifestyle and strengthen their role as promoters of healthy eating. Therefore, the study aims to assess the association between Body Mass Index (BMI), anemia, and dietary diversity among nursing students in Chitwan. MethodsA cross-sectional descriptive study was conducted among 238 bachelor-level nursing students of selected colleges in Chitwan using a census sampling method. Three 24-hour dietary recalls to assess dietary diversity using the Minimum Dietary Diversity for Women (MDD-W) tool, and anthropometric measurements using standard procedures. BMI was categorized using WHO Asian criteria, and hemoglobin was measured with a validated portable HemoCue® HB301device. Data were analyzed in SPSS version 22 using descriptive statistics, one-way ANOVA, and Pearson’s correlation. ResultsThe mean age of the students was 23.39±3.73 years. BMI increased significantly with age and was higher among married and BNS/BMS students, whereas hemoglobin levels did not vary across demographic variables. The mean Dietary Diversity Score was 6.20±1.4, with 82.8% achieving adequate dietary diversity. Overall, 46.6% had normal BMI, 35.2% were overweight/obese, 15.5% underweight, and 55.5% of students were anemic. BMI was weakly correlated with hemoglobin (r=0.158, p-value=0.015), whereas DDS showed no correlation with BMI or hemoglobin level. Conclusions The study revealed that a substantial proportion of nursing students have anemia and are underweight and overweight despite having adequate dietary diversity. BMI was associated with hemoglobin but not dietary diversity, highlighting the need for nutrition counseling and routine BMI and hemoglobin screening to identify at-risk students.